A Technical Note on the Sixth Plan on India (1980-85) - Planning Commission, Government of India (Planning Commission, Government of India, 1980)
The sixth five year plan (1980—85) document presents the strategy and major programmes and policy issues involved in the pursuit of specified objectives. In this note, we present, in more detail, the technical work that went behind the formulation of this plan document.
Government of India Planning Commission
Government of India Planning Commission
Keywords: Sixth Plan- A Technical Note